DEVELOPMENT OF A MULTICULTURAL DIGITAL STORYTELLING FLIPBOOK TO IMPROVE ELEMENTARY STUDENTS’ SPEAKING SKILLS AND TOLERANCE - Salmawati; Nurul Istiqfaroh; M. Bambang Edi Siswanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to develop a multicultural-based Flipbook Digital Storytelling to enhance speaking skills and intercultural social tolerance among third-grade elementary school students. The needs analysis conducted at SDN 017 Penajam revealed that students lacked confidence in speaking, the use of digital media was still low, and learning remained focused on textbooks. In addition, misunderstandings frequently occurred in intercultural interactions. Therefore, an interactive learning media that integrates multicultural values, audio, visuals, and narrative elements is urgently needed. This study involved 96 third-grade students and employed a Research and Development (R&D) design using the ADDIE model. Data were collected through speaking skill tests, social tolerance scales, observations, interviews, and expert validations. Data analysis included qualitative analysis, validity, practicality, and effectiveness assessments. The findings indicate that the developed media is highly valid (material expert = 3.57; language expert = 3.41; media expert = 3.60). It is also highly practical, as shown by teacher responses (92%), student responses (89%), and classroom observations (85%). Speaking skills improved from 63 to 83, while social tolerance increased from 68% to 84%, with an N-Gain score of 0.47. Thus, the multicultural- based Flipbook Digital Storytelling has been proven valid, practical, and effective in improving students’ speaking abilities as well as fostering appreciation and tolerance toward cultural diversity.